Moving objects databases - Guting, Ralf Hartmut, 1955- (Morgan Kaufmann series in data management systems., 2005)
The current trends in consumer electronics--including the use of GPS-equipped PDAs, phones, and vehicles, as well as the RFID-tag tracking and sensor networks--require the database support of a specific flavor of spatio-temporal databases. These we call Moving Objects Databases. Why do you need this book? With current systems, most data management professionals are not able to smoothly integrate spatio-temporal data from moving objects, making data from, say, the path of a hurricane very difficult to model, design, and query. Whether your field is geology, national security, urban planning, mobile computing, or almost anything in between, this books concepts and techniques will help you solve the data management problems associated with this kind of data. + Focuses on the modeling and design of data from moving objects--such as people, animals, vehicles, hurricanes, forest fires, oil spills, armies, or other objects--as well as the storage, retrieval, and querying of that very voluminous data. + Demonstrates through many practical examples and illustrations how new concepts and techniques are used to integrate time and space in database applications. + Provides exercises and solutions in each chapter to enable the reader to explore recent research results in practice. Click here to view more details on Moving Objects Databases (Preface, TOC, Chapter 1, References, etc.).